Shrinkage Analysis on Thick Plate Part using Response Surface Methodology (RSM) - M. Y., Isafiq; Z., Shayfull; S. M., Nasir; Mohd Rashidi, Maarof; M., Fathullah; N. Z., Noriman (Matec Web of Conference, 2016)
The work reported herein is about an analysis on the quality (shrinkage) on a thick plate part using Response Surface Methodology (RSM). Previous researches showed that the most influential factor affecting the shrinkage on moulded parts are mould and melt temperature. Autodesk Moldflow Insight software was used for the analysis, while specifications of Nessei NEX 1000 injection moulding machine and P20 mould material were incorporated in this study on top of Acrylonitrile Butadiene Styrene (ABS) as a moulded thermoplastic material. Mould temperature, melt temperature, packing pressure and packing time were selected as variable parameters. The results show that the shrinkage have improved 42.48% and 14.41% in parallel and normal directions respectively after the optimisation process.